2021
DOI: 10.1089/ees.2020.0262
|View full text |Cite
|
Sign up to set email alerts
|

Improving Life Cycle Economic and Environmental Sustainability of Animal Manure Management in Marginalized Farming Communities Through Resource Recovery

Abstract: A growing world population with increasing levels of food consumption will lead to more dairy and swine production and increasing amount of manure that requires treatment. Discharge of excessive nutrients and carbon in untreated animal manure can lead to greenhouse gas emissions and eutrophication concerns, and treatment efforts can be expensive for small scale farmers in marginalized communities. The overall goal of this study was to determine the environmental and economic sustainability of four animal manur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In addition to quantifying the environmental impacts of anaerobic digestion of wet feedstocks integrated with treatment of liquid (via struvite precipitation or ammonia stripping) and solid digestate (via composting or gasification), studies in Spain, Italy, Belgium, and United Kingdom used CML, ReCiPe, and IPCC to conduct LCA for treating the liquid effluent via constructed wetlands, ,, reverse osmosis, , or sequencing batch reactor for water reuse. Studies in Costa Rica and China assessed anaerobic digestion integrated with struvite precipitation and composting, respectively, for nutrient recovery and lagoon for liquid effluent treatment where animal waste was the feedstock. , A study in the USA utilized municipal sewage sludge to assess the integration of anaerobic digestion, pyrolysis, hydrothermal liquefaction, ammonia stripping, and tertiary treatment of effluent using ReCiPe for LCA and NPV for LCCA/TEA . Generally, fewer LCA and LCCA/TEA studies on the treatment of solid and liquid digestates for RRCC have been completed compared to assessing the environmental and economic impacts of just producing biogas.…”
Section: Applications Of Data Science In Rrcc From Organic Waste Streamsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to quantifying the environmental impacts of anaerobic digestion of wet feedstocks integrated with treatment of liquid (via struvite precipitation or ammonia stripping) and solid digestate (via composting or gasification), studies in Spain, Italy, Belgium, and United Kingdom used CML, ReCiPe, and IPCC to conduct LCA for treating the liquid effluent via constructed wetlands, ,, reverse osmosis, , or sequencing batch reactor for water reuse. Studies in Costa Rica and China assessed anaerobic digestion integrated with struvite precipitation and composting, respectively, for nutrient recovery and lagoon for liquid effluent treatment where animal waste was the feedstock. , A study in the USA utilized municipal sewage sludge to assess the integration of anaerobic digestion, pyrolysis, hydrothermal liquefaction, ammonia stripping, and tertiary treatment of effluent using ReCiPe for LCA and NPV for LCCA/TEA . Generally, fewer LCA and LCCA/TEA studies on the treatment of solid and liquid digestates for RRCC have been completed compared to assessing the environmental and economic impacts of just producing biogas.…”
Section: Applications Of Data Science In Rrcc From Organic Waste Streamsmentioning
confidence: 99%
“…However, considering the large number of studies in the past two decades, a need exists for unified reporting and comparison of such relevant information to appropriately inform practitioners about the effective utilization of data science tools for sustainable RRCC from organic waste streams. Further, although recent studies have demonstrated the potential of integrating multiple technologies to maximally utilize organic waste and recover a variety of resources, [13][14][15]47,48 a literature review of data science applications in such integrated RRCC technologies has yet to be conducted. The overall goal of this study is to conduct a critical literature review covering the wide umbrella of data science applications that includes data-driven process modeling along with the environmental and economic impact assessments in RRCC from multiple organic waste streams through single or multiple-treatment technologies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production processes of these critical substances are however, energy‐intensive and account for significant CO 2 emission 1,3 . In particular, ammonia production via the conventional Haber‐Bosch process accounts for ~1.4% global CO 2 emission, 3,4 whereas approximately 1 ton of CO 2 is generated for a kilogram of phosphorus fertilizer production 5 . In addition, excessive nutrient loads discharged to the environment from waste streams can result in harmful algal blooms, causing impacts on aquatic ecosystems, fisheries, recreation, water supplies, and public health, 6 via a process called eutrophication.…”
Section: Introductionmentioning
confidence: 99%